Rehabilitasi Neuropsikologi Dalam Upaya Memperbaiki Defisit Executive Function (Fungsi Eksekutif) Klien Gangguan Mental - Nur Fatwikiningsih (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2016)
Executive function is responsible for directing self behavior in order to purposive and aims such as planning, organizing, problem solving, self-monitoring skills and self regulation. This function is associated with frontal lobe (center of think). The main components of executive function are anticipation (set realistic expectations, understanding the consequences), planning (organization), execution or implementation (maintain flexibility), self-monitoring (emotional control, error recognition). Dysfunction executive (deficit of executive functions) is one cause of disability in the client's mental disorders so that clients of mental disorders commonly have difficulty in performing activities of complex psychological like behavior of complex, purposeful, targeted and selective attention, decision-making, judgment, selection, planning, and flexibility. Neuropsychological rehabilitation efforts can be used to improve executive function (executive function) thus will significantly improve emotional health, social functioning, and independent skill. The rehabilitation program consists of a variety of techniques that include Cognitive Adaptation Training (CAT), verbalization, goal setting and cognitive remediation.